The perspective of the acting person : essays in the renewal of thomistic moral philosophy - Rhonheimer, Martin, 1950-, autor; Murphy, William F., editor literario (Catholic University of America Press, 2008)
The Perspective of the Acting Person introduces readers to one of the most important and provocative thinkers in contemporary moral philosophy. In this collection of essays Martin Rhonheimer examines the central themes of natural law, moral action, and virtue emphasized by John Paul II's 1993 encyclical Veritatis Splendor. Rhonheimer's work follows the general direction taken by the encyclical through an almost unprecedented rigor of philosophical argumentation and level of engagement with both European and American scholarship.